Investigate the Effects of Industrial Agglomeration on Nitrogen Dioxide Pollution Using Spatial Panel Durbin and Panel Threshold Models - Han, Cheng-Yu; Gu, Zhao-Lin; Yang, Hexiang (Frontiers in Environmental Science, 2022)
The degree of industrial agglomeration in China has contributed to the reduction of nitrogen dioxide pollution because of financial support, the allocation of environmental governance efficiency, and technological advantages. However, the intensity and scope of the spatial effect of this contribution need to be studied in depth. Based on the influence mechanism and intermediate mechanism of the spatial pattern, this paper uses the panel data of 282 prefecture-level and above cities in China from 2015 to 2018, draws on the STIRPAT model, uses the Spatial Panel Dubin (SDM) model and Panel Threshold (PTR) model to investigate the effects of industrial agglomeration on nitrogen dioxide. The study found that: (1) industrial agglomeration has a significant spatial spillover effect on the reduction of nitrogen dioxide pollution, and the increase in the level of local industrial agglomeration can greatly reduce the concentration of nitrogen dioxide in the surrounding area. (2) This kind of spatial overflow has a threshold boundary. Within 100 kilometers, it is a dense area of overflow and reaches the threshold boundary beyond 150 kilometers. (3) Under the influence of the three intermediate mechanisms of industrial agglomeration, the increase in car ownership, and the level of economic development, the impact of industrial agglomeration on the reduction of nitrogen dioxide pollution has gradually increased. The above conclusion is still valid after various robustness tests.